The People of the Song : Biblical Poetry, Translation, and the Reception of Moses Mendelssohn in the Berlin Haskalah - Sela, Yael, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
When, in 1783, Moses Mendelssohn's German Psalms translation was published in Berlin, forward-thinking ideologues of Jewish cultural revival rendered its translator a redeemer of the songs of King David from exilic desolation. The People of the Song is the first study to examine Mendelssohn's conception of biblical Hebrew poetry as a particular manifestation of Judaism's universalism. The author traces how it helped forge a new foundational narrative that imagined Israel's covenant with God in sacred song, not in revealed law, portrayed King David as a bard, not a military leader, and envisioned national redemption of modern Jews as an aesthetic, not a political, revival.